Comparison of TOPSIS and MAUT methods for recipient determination home surgery - Septya Maharani; Holis Ridwanto; Heliza Rahmania Hatta; Dyna Marisa Khairina; Muhammad Rivani Ibrahim (Institute of Advanced Engineering and Science, 2021)
House renovation is given by the government to the community, one of which is the assistance provided in the district. Long Mevery especially Tanah Abang Village, namely House Renovation Assistance. So it is necessary to implement a DSS in determining the recipient of home renovation assistance by comparing MAUT method and TOPSIS to assist the government in determining the right home renovation assistance recipient. There are 16 criteria and their weight values. This study uses the multi-attribute utility theory method (MAUT) and the order of preference technique based on the similarity to the ideal solution (TOPSI) as a calculation method to produce output and determine the level of accuracy of each method. The test in this study uses a confusion matrix and compares real data testing with the results of calculations on the system. The results of system testing using MAUT and TOPSIS methods, the accuracy of the MAUT method is 94.28% and the TOPSIS method is 35.71%.